Um ambiente, tantas verdades : estudo sociológico dos discursos científicos sobre a represa do Lobo/Broa - Campregher, Raiza (2016)
The emergence of the environmental issues, from the 1960s, represented significant changes in the way societies perceive the environment, in particular through the process of politicization of nature. In this sense, the present work understands the modern environmental issues as a social construction disputed through the production of discourses about the environment. Thus, it aims to comprehend the production of scientific discourses about Lobo/Broa dam, as well as its specific effects of power. Lobo/Broa dam, in São Paulo state, is a small reservoir for hydroelectric energy production, also used for recreation, and as a lab for research on ecology and hydraulic engineering. The research hypothesis lays on the idea that scientific discourse about the reservoir’s environment works as “truth”, exerting the effects of power associated with this condition. The methodology of the research consists in case study and qualitative methods of social research, including bibliographic and documentary research and semi-structured interviews.